Workplace Violence against Paramedical Staff at a Moroccan University Hospital - Laadraoui, F.; Zeggwagh, A. A. (Indian Journal of Nursing Sciences, 2024)
Aim: The aim was to determine the prevalence of patient violence against paramedical staff in a university hospital, and the factors that contribute to it. Materials and Methods: This is a cross-sectional and observational study conducted from April 2018 to April 2019 among nurses and health technicians in various departments of a university hospital. The self-questionnaire included indicators of violence experienced in the past 12 months. It consists of seven items and 49 questions. Results: The participation rate was 71%. The average age was 42 ± 13 years and professional seniority 16 ± 12 years. The prevalence of violence was 79% (95%, CI: 74.8–82.9%). The prevalence of verbal violence was 79% (n = 324) and that of physical violence 32.2% (n = 132). The most frequent forms of physical violence were spitting and pushing, observed in a third of cases each, followed by damage to equipment in a quarter of cases. As for verbal abuse, the most frequent were insults (80.6%), shouting (63.3%), and verbal threats (44.4%). Accompanying staff were responsible for the violence. The main consequences of violence on staff health were: Stress (70.1%), feelings of insecurity (62.7%), anxiety (57.1%), depression (37%), and demotivation (52.8%). Independent factors favoring violence were: Professional seniority ≤5 years and working in a department in direct contact with patients and their careers. Conclusion: Violence is a common problem in hospitals. The staff most at risk are those with the least experience. The development and implementation of preventive strategies against violent incidents for the benefit of staff, and specifically at-risk staff, are essential.